Ap2s1 mutation causes hypercalcaemia in mice and impairs interaction between calcium-sensing receptor and adaptor protein-2. Issue 10 (17th March 2021) - Hannan, Fadil M; Stevenson, Mark; Bayliss, Asha L; Stokes, Victoria J; Stewart, Michelle; Kooblall, Kreepa G; Gorvin, Caroline M; Codner, Gemma; Teboul, Lydia; Wells, Sara; Thakker, Rajesh V
Abstract: Adaptor protein 2 (AP2), a heterotetrameric complex comprising AP2α, AP2β2, AP2μ2 and AP2σ2 subunits, is ubiquitously expressed and involved in endocytosis and trafficking of membrane proteins, such as the calcium-sensing receptor (CaSR), a G-protein coupled receptor that signals via Gα11 . Mutations of CaSR, Gα11 and AP2σ2, encoded by AP2S1, cause familial hypocalciuric hypercalcaemia types 1–3 (FHH1–3), respectively. FHH3 patients have heterozygous AP2S1 missense Arg15 mutations (p.Arg15Cys, p.Arg15His or p.Arg15Leu) with hypercalcaemia, which may be marked and symptomatic, and occasional hypophosphataemia and osteomalacia. To further characterize the phenotypic spectrum and calcitropic pathophysiology of FHH3, we used CRISPR/Cas9 genome editing to generate mice harboring the AP2S1 p.Arg15Leu mutation, which causes the most severe FHH3 phenotype. Heterozygous ( Ap2s1 +/L15 ) mice were viable, and had marked hypercalcaemia, hypermagnesaemia, hypophosphataemia, and increases in alkaline phosphatase activity and fibroblast growth factor-23. Plasma 1, 25-dihydroxyvitamin D was normal, and no alterations in bone mineral density or bone turnover were noted. Homozygous ( Ap2s1 L15/L15 ) mice invariably died perinatally. Co-immunoprecipitation studies showed that the AP2S1 p.Arg15Leu mutation impaired protein–protein interactions between AP2σ2 and the other AP2 subunits, and also with the CaSR. Cinacalcet, a CaSR positive allosteric modulator, decreased plasma calcium and parathyroid hormone concentrations in Ap2s1 +/L15 mice, but had no effect on the diminished AP2σ2-CaSR interaction in vitro . Thus, our studies have established a mouse model that is representative for FHH3 in humans, and demonstrated that the AP2S1 p.Arg15Leu mutation causes a predominantly calcitropic phenotype, which can be ameliorated by treatment with cinacalcet.